The economic sociology of development - Schrank, Andrew (Cambridge, [England] Polity Press, 2023)
Schrank draws concrete examples from different regions and epochs to explore sociological thinking about development and underdevelopment informed by the latest currents in economic sociology. Across a series of chapters, he identifies relationships between mainstream and Marxist approaches to the study of international inequality; uses classical and contemporary social theory to develop a parsimonious typology of national development outcomes; addresses cross-border learning and diffusion in light of the latest developments in organisation theory; considers the roles of religious, racial, and gender identity in driving development in different places and times; and portrays contemporary global challenges - such as populism, pandemics, and climate change - as distinctly sociological problems in need of multifaceted solutions.
1. Introduction -- 2. What Do We Mean by "Development?" -- 3. Is International Inequality Gradational or Relational? -- 4. Explaining National Mobility in the Cold War Era -- 5. The Diffusion and Demise of Free-Market Reform in the Post-Cold War Era -- 6. What If Sociologists Were in Charge?
Includes bibliographical references (pages 176-225) and index.
Keywords: Economics -- Sociological aspects; Development economics -- Social aspects